Spontaneous hemoperitoneum - B. Varela, Nelson (Cirugía del Uruguay, 1971)
Three cases of spontaneous hemoperitoneum are reported. They presented the following common features: 1) they began as an acute abdomen; 2) they presented evident anemia; 3) bleeding was the first clinic demonstration of the illness; 4) there was a preexistant pathologic condition and it was evident in the operation. Considerations about etiology diagnosisand treatment are described.